Differentiation of local tumor recurrence from radiation-induced changes after stereotactic radiosurgery for treatment of brain metastasis: case report and review of the literature - Kickingereder, Philipp (BioMed Central, 2013)
BACKGROUND: Structural follow-up magnetic resonance imaging (MRI) after stereotactic radiosurgery (SRS) for brain metastases frequently displays local changes in the area of applied irradiation, which are often difficult to interpret (e.g., local tumor recurrence, radiation-induced changes). The use of stereotactic biopsy for histological assessment of these changes has a high diagnostic accuracy and can be considered as method of choice. In order to solve this relevant clinical problem non-invasively, advanced MRI techniques and amino acid positron-emission-tomography (PET) are increasingly used. CASE PRESENTATION: We report the long-term follow-up of a patient who had been treated with linear accelerator based SRS for cerebral metastases of a lung cancer. Fifty-eight months after SRS, the differentiation of local recurrent brain metastasis from radiation-induced changes using structural MRI was difficult. For further differentiation, perfusion-weighted MRI (PWI), proton magnetic resonance spectroscopy (MRS), and (11)C-methyl-L-methionine (MET) PET was performed. Due to artifacts and technical limitations, PWI MRI and MRS findings were not conclusive. In contrast, MET PET findings were suggestive for radiation-induced changes. Finally, a stereotactic biopsy for histological assessment of these changes demonstrated clearly a radiation-induced necrosis and the absence of vital tumor. CONCLUSION: The use of stereotactic biopsy for histological assessment of indistinguishable lesions on structural MRI after SRS for treatment of brain metastasis represents a highly reliable method to differentiate local tumor recurrence from radiation-induced changes. In this field, results of studies with both advanced MRI techniques and amino acid PET suggest encouraging results. However, artifacts and technical limitations (e.g., lesion size) are still a problem and comparative studies are needed to investigate the relationship, diagnostic performance, and complementary character of advanced MRI techniques and amino acid PET.